Layanan Konsultasi Padi Indonesia - Jardinero, Benedict; Argosubekti, Nuning; Sembiring, Hasil; Casimero, Madonna (International Rice Research Institute, 2025)
"Rice Crop Manager Indonesia, known locally as Layanan Konsultasi Padi (LKP), was developed and introduced to address the key challenges for rice production and productivity in Indonesia through site-specific recommendations leading to a proven increase in yields and incomes. LKP is a digital agriculture decision support tool developed by the International Rice Research Institute to identify the best nutrient management practices for specific rice fields using site-specific nutrient management principles. LKP is designed for use by extension workers, crop advisors, input providers, and providers of services who interview a farmer using a computer or smartphone. Collected information is used to calculate recommendations and transformed into a crop management guideline for the farmer in a one page printout. Each guideline provides an actionable recommendation, which matches the locationspecific cropping practices and needs of a farmer."